Ag/white graphene foam for catalytic oxidation of methanol with high efficiency and stability1. Issue 12 (28th March 2015) - Zhao, Huijie; Song, Jizhong; Song, Xiufeng; Yan, Zhong; Zeng, Haibo
<x xml:space="preserve">Abstract</x> Oxidation of methanol not only eliminates contamination due to typical volatile organic compounds (VOCs), but also provides clean energy.